The post-crisis TFP growth slowdown in CEE countries: Exploring the role of Global Value Chains - Francesco Chiacchio; Katerina Gradeva; Paloma López-García (European Central Bank (ECB), 2018)
Using micro-aggregated firm information for nine Central and Eastern European (CEE) countries and data from input-output tables, we examine the role of Global Value Chains (GVCs) for technology diffusion across EU countries. Our empirical results provide support for a two-stage diffusion process of technology across countries. In the first stage, the most productive firms in the host economy benefit from their direct exposure to new technology created in parent firms as a result of their GVC participation. In the second stage, technology spills over to the rest of firms in the host economy via domestic production networks. In addition, we show that the import of intermediate inputs - i.e. backward linkages - is the main channel of technology diffusion within GVCs. We use these results to explain the pronounced post-crisis drop in Total Factor Productivity (TFP) growth in CEE countries. We show that due to their deep integration in GVCs, CEE countries have been exposed to two recent developments highly correlated with their TFP performance: (i) a slowdown in TFP growth of parent firms located in non-CEE EU countries; and (ii) a global slowdown in the growth rate of GVC participation, which is evident also for CEE countries from 2011 onwards. Moreover, we find that the capacity of host firms in CEE countries to absorb and understand new knowledge has decreased since the crisis. We argue that this is related to the drop in R&D investment in the CEE region during the post-crisis period.
Keywords: O33; O47; O57; C33; 330; TFP growth; Global Value Chains; technology diffusion; Central and Eastern Europe